The Impact of Internal Audit Effectiveness on Financial Reporting Quality: Evidence from Rural Banks (BPRs) in Tabanan Regency - Bevi Libraeni; Mila Rosa Desmayani; Nonik Erawati (PT. Altaf Publishing Corp, 2026)
This study aims to examine the role of internal auditors in improving the quality of financial reporting. High-quality financial reporting is essential because it provides reliable information that serves as the basis for decision-making by management, investors, creditors, and other stakeholders. Therefore, ensuring the accuracy, transparency, and reliability of financial reports is crucial. In recent years, the role of internal auditors has received increasing attention as one of the key factors contributing to the enhancement of financial reporting quality through effective internal control and oversight. This research employs a quantitative approach using primary data collected through questionnaires distributed to internal auditors of Rural Banks (BPRs) located in Bandung City, Bandung Regency, and West Bandung Regency. The sampling technique applied was purposive sampling, resulting in a sample of 24 BPRs. A total of 24 questionnaires were distributed, of which 24 were returned and deemed suitable for analysis. The collected data were analyzed using simple linear regression. Prior to the regression analysis, the research instrument was tested for validity and reliability to ensure the accuracy and consistency of the questionnaire. The findings reveal that internal auditors have a positive and statistically significant effect on the quality of financial reporting. The coefficient of determination (R²) indicates that internal auditors account for 72.3% of the variation in financial reporting quality, while the remaining 27.7% is explained by other factors not included in the study. These results suggest that a higher level of internal auditor involvement in monitoring and evaluating the financial reporting process leads to improved financial reporting quality. Consequently, the effectiveness of internal audit functions plays a vital role in promoting transparent, reliable, and accountable financial reporting.